2013
DOI: 10.1002/esp.3484
|View full text |Cite
|
Sign up to set email alerts
|

Marking time in Geomorphology: should we try to formalise an Anthropocene definition?

Abstract: The value of a formally defined Anthropocene for geomorphologists is discussed. Human impacts have been diachronistic, multifaceted and episodic, as demonstrated by the record of alluvial deposition in the UK. Rather than boxing time into discrete eras or periods, modern research uses calendar dates and multiple dating techniques to explore co-trajectories for a range of human impacts. Despite the value of 'The Anthropocene' as an informal concept and as a prompt to useful debate, arriving at a single, general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Others have suggested that the complexities of human history mean that the term 'Anthropocene' is best used informally, as it is now, and that formalization would be a distraction [2,21,24]. However, given the wide range of different human impacts and time periods that the term is currently applied to, it is hard to see how this 'informality' aids communication.…”
mentioning
confidence: 92%
“…Others have suggested that the complexities of human history mean that the term 'Anthropocene' is best used informally, as it is now, and that formalization would be a distraction [2,21,24]. However, given the wide range of different human impacts and time periods that the term is currently applied to, it is hard to see how this 'informality' aids communication.…”
mentioning
confidence: 92%
“…Further geoarchaeological analysis is being undertaken on the alluvial sequence at Wellington Quarry, but if chronological continuity can be applied to the formation of these key stratigraphic units, then wider factors such as climate variability and land-use narratives can be investigated through these fluvial archives. Integration of the Lugg sequences with work from the Rivers Arrow, Frome and Wye within adjacent catchments of the West Midlands has the potential to allow development of inter-regional valley geochronologies and to input into national and international debates concerning the stratigraphic signal of the Anthropocene (Gales and Hoare, 2012;Lewin and Macklin, 2014). The results of this ongoing work also provide a basis and opportunity for beginning to compare the geoarchaeological records and preservation potential of lowland river systems with those of the piedmont and upland zone, which have different late Pleistocene and Holocene evolutionary histories (Howard and Macklin, 1999).…”
Section: Chronological Evolution and Wider Implicationsmentioning
confidence: 99%
“…The aim here, therefore, is to use the idea of the Anthropocene as a lens through which geomorphologists can develop research which contributes more directly to a better understanding of the relationship between society and landforms and the processes that shape them. Brown et al (2013) suggest that there could well be a 'geomorphological case' for the Anthropocene and Lewin and Macklin (2013) have already assessed the possible value of a formally defined Anthropocene for geomorphologists. Whether we recognise the Anthropocene or not, further exploration is still needed of the nature and magnitude of societal impact on geomorphic processes in a variety of geographical contexts and at a range of scales.…”
Section: Introduction: the Anthropocenementioning
confidence: 98%